2014
DOI: 10.4067/s0717-95532014000300010
|View full text |Cite
|
Sign up to set email alerts
|

La Familia Y El Consumo De Alcohol en Estudiantes Universitarios

Abstract: RESUMENEl consumo de alcohol constituye un problema de salud pública por la alta prevalencia del consumo, la mortalidad y trastornos mentales asociados a éste, principalmente en los jóvenes. Objetivo: Identificar la relación e influencia de la historia familiar de consumo de alcohol sobre el consumo de alcohol en los estudiantes universitarios. Material y método: El estudio fue descriptivo, correlacional y predictivo. La población fueron estudiantes universitarios. El muestreo fue aleatorio estratificado con a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
0
3
0
16
Order By: Relevance
“…In Mexico, it has been found that approximately 60% of the adult population age 18-65 has a family history of alcohol use, that is, has a father or mother who drinks frequently or habitually (Natera-Rey, Borges, Medina-Mora, Solis-Rojas, & Tiburcio-Sainz, 2001). A study in Nuevo Leon found that 80% of junior high school students in that state had such a history (Armendáriz et al, 2014). A study of adolescents in Tabasco reported that 56.8% lived with someone who used alcohol, most commonly the father (38.8%), followed by both parents (24.5%), the mother (13.7%), and siblings (10.8%) (Telumbre, López, Sánchez, Magnolia-Araujo, & Torres, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico, it has been found that approximately 60% of the adult population age 18-65 has a family history of alcohol use, that is, has a father or mother who drinks frequently or habitually (Natera-Rey, Borges, Medina-Mora, Solis-Rojas, & Tiburcio-Sainz, 2001). A study in Nuevo Leon found that 80% of junior high school students in that state had such a history (Armendáriz et al, 2014). A study of adolescents in Tabasco reported that 56.8% lived with someone who used alcohol, most commonly the father (38.8%), followed by both parents (24.5%), the mother (13.7%), and siblings (10.8%) (Telumbre, López, Sánchez, Magnolia-Araujo, & Torres, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the significant findings in this study was that the prevalence of ever having used alcohol and that of having used it in the previous month differed according to family history (χ 2 = 13.04, p = .001; χ 2 = 7.32, p = .007, respectively). Armendáriz et al (2014), in a study of 680 university students in the state of Nuevo Leon, found that a family history of alcohol use influenced the students' own use (B = .080, p = .001). A subsequent study, with 240 high school students in the same state, found that greater alcohol use by parents was associated with an increased use by their children (rs = .196; p < .01) (Armendáriz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Con relación a los factores del ámbito familiar, algunos estudios mencionan que los adolescentes que no usan alcohol o que consumen poco presentan mayor comunicación con sus padres (Cid-Monckton & Pedrão, 2011;Oman et al, 2004;Solórzano et al, 2016), más supervisión por parte de ellos y mejores vínculos parentales (Andrade, Sánchez-Xicoténcatl, Demetrio, Gonzá-lez, & Betancourt, 2015;Bobakova, Madarasova, Klein, Reijneveld, & Van Diijk, 2012;Kaynak et al, 2013;Light, Greenan, Rusby, Nies, & Snijders, 2013;Martínez & Robles, 2001), así como menos ingesta de alcohol de los padres (Armendáriz et al, 2014;Bobakova et al, 2012;Espada, Pereira, & García-Fernández, 2008;Glanton & Wulfert, 2013;Handley & Chassin, 2013;Lema, Varela, Duarte, & Bonilla, 2011).…”
Section: Introductionunclassified
“…Estes discursos perpassam o contexto da família e intensificam o sofrimento por meio da culpabilização frente ao fato de ter um de seus membros usuário de drogas. 3 5 A perspectiva construcionista da realidade entende que o conhecimento resulta de uma construção social, da interação humana datado de um certo período histórico, isto é, o conhecimento se produz na coletividade e na intersubjetividade/interpessoalidade. 5 A escolha pelo método deve-se ao fato de se tratar de um tema que nos instiga a refletir sobre diversos discursos produzidos neste âmbito, os quais se reinscrevem continuamente no nosso cotidiano e produzem modos de ser e estar implicados no sofrimento e adoecimento nos jovens do contemporâneo.…”
Section: Introductionunclassified